1987
DOI: 10.1088/0031-8949/35/6/004
|View full text |Cite
|
Sign up to set email alerts
|

Quartet Term Systems of C3+–F6+Ions

Abstract: The C IV, N V, O VI and F VII quartet term systems have been investigated using the beam-foil method, Wavelengths of more than 70 lines associated with these systems are reported. They are compared to theoretical predictions and to data on analogous transitions in singly excited four-electron ions.Certain details of the term structure are discussed as are fine structure splittings and the separations of quartet terms arising from electron configuration 1s2p3p, 1s2p3d, and 1s2p4d. In the isoelectronic compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
6
23
0
Order By: Relevance
“…As Table II shows, the transition wavelengths in this work are in good agreement with other theoretical predictions and experimental results. beam-foil method [3]. For the F 6þ ion, the transition wavelength between 1s2p2p 4 P(1) and 1s2p3s 4 P o (3) is 11.879 nm, which is the same as the result of Blank et al [3].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…As Table II shows, the transition wavelengths in this work are in good agreement with other theoretical predictions and experimental results. beam-foil method [3]. For the F 6þ ion, the transition wavelength between 1s2p2p 4 P(1) and 1s2p3s 4 P o (3) is 11.879 nm, which is the same as the result of Blank et al [3].…”
Section: Resultssupporting
confidence: 72%
“…beam-foil method [3]. For the F 6þ ion, the transition wavelength between 1s2p2p 4 P(1) and 1s2p3s 4 P o (3) is 11.879 nm, which is the same as the result of Blank et al [3]. Figure 1 shows the energy-level and transition wavelength diagram for high-lying core excited quartet states 1s2lnl The relativistic energies given in Table I are the center-of-gravity energies.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…We construct a model-potential VM for the K-shell electron which is such that the eigenvalues sot of the 1-electron Schr6dinger equation (-½ V 2 + VM) 4.~ = ~.~ ~.~ (1) reproduce the ionisation energies of the triplet l snI 3L levels of N VI. The potential V~ which we use,…”
Section: Theorymentioning
confidence: 99%
“…Beam-foil studies of the quartet term system of the lithium-like ion NV have recently been reported by Blanke et al [1,2] and by Garnir et al [3,4]. In addition, Bouchama et al [5] have employed an interesting new technique, based on charge exchange in a gas cell, to investigate the quartet spectrum of NV.…”
Section: Introductionmentioning
confidence: 99%